Information behaviour of university students: a literature review (Libellarium: journal for research in the field of information and related sciences, 2015)
This literature review attempts to give an overview of the field of university students' information behaviour. Students are generally one of the most investigated groups in the field of human information behaviour, but the field of students' information behaviour is difficult to draw into a coherent knowledge base. There are many studies of different aspects of information behaviour conducted over different groups of students. This paper presents some of the key conclusions and perspectives of selected studies. Studies in this field are conducted from the beginning of 1970's when the focus was on exploring the usage of library resources and services. During the last two decades the interest in students' library use and information behaviour in general has increased and the focus of research expanded. This review presents the literature in the following main areas: disciplinary differences in information seeking and use, the impact of curriculum and wider context including learning and teaching, effects of personality attributes, and studies that focus on use of electronic information resources. This paper also highlights research problems that authors suggest as topics for further studies.
Keywords: information behaviour; university students; user studies